2021
DOI: 10.2337/dc20-2439
|View full text |Cite
|
Sign up to set email alerts
|

Historical HbA1c Values May Explain the Type 2 Diabetes Legacy Effect: UKPDS 88

Abstract: Type 2 diabetes all-cause mortality (ACM) and myocardial infarction (MI) glycemic legacy effects have not been explained. We examined their relationships with prior individual HbA 1c values and explored the potential impact of instituting earlier, compared with delayed, glucose-lowering therapy. RESEARCH DESIGN AND METHODSTwenty-year ACM and MI hazard functions were estimated from diagnosis of type 2 diabetes in 3,802 UK Prospective Diabetes Study participants. Impact of HbA 1c values over time was analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 35 publications
(72 reference statements)
1
41
0
4
Order By: Relevance
“…Attaining recommended glycaemic targets yields substantial and enduring reductions in the onset and progression of microvascular complications [ 11 , 12 ] and early intervention is essential [ 13 ]. The greatest absolute risk reduction comes from improving very elevated glycaemic levels, and a more modest reduction results from near normalisation of plasma glucose levels [ 2 , 14 ].…”
Section: The Rationale Importance and Context Of Glucose-lowering Tre...mentioning
confidence: 99%
“…Attaining recommended glycaemic targets yields substantial and enduring reductions in the onset and progression of microvascular complications [ 11 , 12 ] and early intervention is essential [ 13 ]. The greatest absolute risk reduction comes from improving very elevated glycaemic levels, and a more modest reduction results from near normalisation of plasma glucose levels [ 2 , 14 ].…”
Section: The Rationale Importance and Context Of Glucose-lowering Tre...mentioning
confidence: 99%
“…Thirdly, our findings add weight to the importance of early and strict metabolic control in T2DM. Two post hoc analyses of the UKPDS study have shown that the glycemic legacy effects seen in T2DM are largely explained by historical HbA1c values, which have a greater impact on renal and cardiovascular outcomes than recent values; microvascular complications and mortality also increased in those patients who presented HbA1c >6.5% in the first year after diagnosis [ 21 , 22 ]. Based on our findings and supported by these post hoc studies, we could suggest that early detection of diabetes and intensive glucose control from the time of diagnosis are essential for maximum reduction of long-term risk of glycemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Die Autoren schlussfolgern, dass historische Glukosewerte, vor allem in der Phase der ersten Jahre der Behandlung, die Prognose des Typ-2-Diabetes deutlich stärker beeinflussen als die nachfolgenden bzw. aktuellen Glukosewerte, und fordern eine frühe Diabetesdiagnose und eine möglichst normnahe Glukosekontrolle vor allem zu Beginn der Diabetestherapie [51].…”
Section: Langzeitprognose: Ergebnisse Großer Interventionsstudienunclassified